Standard operating procedure for surveillance of sporotricosis epizooties in Ponta Grossa/PR (Research, Society and Development, 2022)
Sporotrichosis is a fungal disease caused by the dimorphic fungus Sporothrix spp., which affects mammals, mainly cats and humans. Its distribution is worldwide and, in Brazil, its occurrence is mainly associated with zoonotic transmission by infected domestic cats, with cases distributed in several regions of the country. In the city of Ponta Grossa-PR, the first case of sporotrichosis in a cat occurred in 2020, making it necessary to create a protocol for coping and surveillance of this zoonosis to prevent its spread. The present study aimed to report the standard operating procedure created for the municipality, which had three distinct work fronts: awareness of health professionals; establishment of internal protocols and documents for investigation and conduct; and health education. Until December 2021, there were 10 cases of sporotrichosis in cats in the city. It is concluded that the standard operating procedure was necessary for the direction of decision-making, being essential in the control, prevention and identification of new cases of this epizootic, in order to prevent it from becoming a serious public health problem in the city of Ponta Grossa-PR.